2019
DOI: 10.3892/ol.2019.10381
|View full text |Cite
|
Sign up to set email alerts
|

Leptin contributes to the taxol chemoresistance in epithelial ovarian cancer

Abstract: Epithelial ovarian cancer (EOC) is a gynecological malignancy with high morbidity. Treating EOC remains a challenge, as the pathogenesis of this disease remains unclear and chemoresistance is a common occurrence. A number of previous studies have revealed that obesity is closely associated with cancer and leptin, as a link between cancer and obesity, has become a focus of research in recent years. In the present study, survival database analysis demonstrated that leptin expression was associated with poor prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…The influence of leptin on chemoresistance in epithelial ovarian cancer has been studied. Treatment with exogenous leptin decreased paclitaxel/docetaxel-induced G2/M phase cell cycle arrest in ovarian cancer cells [ 36 ]. However, experimental results from another research group showed that serum levels of leptin were not correlated with the response to paclitaxel/carboplatin therapy in ovarian cancer patients [ 37 ].…”
Section: Lep Somatic Mutations and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of leptin on chemoresistance in epithelial ovarian cancer has been studied. Treatment with exogenous leptin decreased paclitaxel/docetaxel-induced G2/M phase cell cycle arrest in ovarian cancer cells [ 36 ]. However, experimental results from another research group showed that serum levels of leptin were not correlated with the response to paclitaxel/carboplatin therapy in ovarian cancer patients [ 37 ].…”
Section: Lep Somatic Mutations and Cancermentioning
confidence: 99%
“…The demonstrations of main biological effects (Table 2) and signaling axes (Figure 4) induced by leptin/leptin receptor in different cancer types were shown. Ovarian Cancer ↑: [41] ↑: [38][39][40]42] ↑: (paclitaxel/docetaxel) [36] Brain Tumor ↑: [45,46] ↑: [47,48] ↑: [45] ↑: (temozolomide) [49] Breast Cancer ↑: [54,58] ↑: [53,55] Liver Cancer ↑: [60,63] ↑: [60,63] ↓: [63] ↓: [65] (rat)…”
Section: Leptin and Other Types Of Cancermentioning
confidence: 99%
“…Hence, the incubation of leptin with OC cells ameliorates the influence of paclitaxel/Taxol on cancer cell microtubules. It is worth mentioning that high levels of leptin hypothetically may have linkage with resistance to chemotherapy, but these data are unclear and need further research [ 111 ].…”
Section: Role Of Adipokinesmentioning
confidence: 99%
“…The main mechanism of adipocyte-induced therapy resistance is to modulate the pro-survival pathways and survival genes. It was reported adipocyte-secreted leptin contributed to the taxol chemoresistance in EOC through the activation of EMT in ovarian cancer cells [ 124 ]. Leptin could also activate AKT and ERK survival pathways in EOC cells, which are known to play crucial roles in EOC drug resistance [ 125 ].…”
Section: Adipocytes and Ovarian Cancer Treatmentmentioning
confidence: 99%